2020
DOI: 10.1155/2020/3708231
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of an Energy Metabolism-Related lncRNA-mRNA Signature for Lower-Grade Glioma

Abstract: Energy metabolic processes play important roles for tumor malignancy, indicating that related protein-coding genes and regulatory upstream genes (such as long noncoding RNAs (lncRNAs)) may represent potential biomarkers for prognostic prediction. This study will develop a new energy metabolism-related lncRNA-mRNA prognostic signature for lower-grade glioma (LGG) patients. A GSE4290 dataset obtained from Gene Expression Omnibus was used for screening the differentially expressed genes (DEGs) and lncRNAs (DELs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…The lncRNAs play a crucial role in transcriptional regulation, epigenetic gene regulation, and disease, a kind of non-coding RNAs greater than 200 nucleotides, with no protein-coding function (10,11). With the deepening of research, the relationship between lncRNA and progression, metastasis, and prognosis of various tumors has been found, such as the digestive, nervous, bone, and urinary system (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNAs play a crucial role in transcriptional regulation, epigenetic gene regulation, and disease, a kind of non-coding RNAs greater than 200 nucleotides, with no protein-coding function (10,11). With the deepening of research, the relationship between lncRNA and progression, metastasis, and prognosis of various tumors has been found, such as the digestive, nervous, bone, and urinary system (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Although maximum surgical resection, radiotherapy and chemotherapy are considered as the main strategies combating LGG, tumor metastasis, recurrence and patient death cannot be completely prevented [8]. Therefore, there is a need to further explore additional tools for the diagnosis treatment and prognosis of LGG and to develop new risk factors and molecular markers for early strati cation of low-and high-risk patients with preventive treatment [9]. In this context, identifying high-risk LGG individuals with unsatisfying outcome turns out an essential work that needs to be concerned.…”
Section: Introductionmentioning
confidence: 99%
“…The AUC of HRLscore in survival prediction was generally higher than that of each clinicopathologic feature, and addition of the HRLscore to these variables could improve the prognostic performance (Supplementary Table 2). Furthermore, we compared the predictive accuracy of HRLscore versus several multigene signatures in existing publications by Zhang ret al ( 27), Wang et al (28), and Zhao et al (29). The result demonstrated that the HRLscore was not inferior to other three prognostic models in the TCGA-LGG cohort (Supplementary Figure 5).…”
Section: Prognostic Performance Of Hrlscore Versus Other Predictorsmentioning
confidence: 76%
“…Also for LGG, increasing studies have focused on establishing prognostic gene models based on mRNA, lncRNA, or proteomic approaches. For example, Zhao et al (29) recently constructed a metabolism-related lncRNA-mRNA that could predict the clinical outcomes of LGG patients. In our study, we have compared the prognostic accuracy of HRLscore and other multigene models from previous publications (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation